Forms and Field Trials of a Digital Evaluation Tool: Integrating F-S Model, WP Method, and Balinese Local Wisdom for Effective E-Learning - Ariawan, I Putu Wisna; Sugandini, Wayan; Ardana, I Made; Sugiharni, Gusti Ayu Dessy; Gama, Adie Wahyudi Oktavia; Divayana, Dewa Gede Hendra (Bright Publisher, 2024)
This study purposed to show the tool display and the results of field trials on the digital evaluation tool. This tool is an evaluation tool in digital format which was from a combination of the concept of the educational evaluation model “F-S (Formative-Summative)”, the decision support system method “WP (Weighted Product)”, and Balinese local wisdom “TP (Tri Pramana)”. The importance of combining these concepts and methods is it makes it easier to obtain accurate calculation results following the needs of evaluation tools to determine the dominant aspects determining the effectiveness of e-learning. This research approach was development research. The development model was Borg and Gall, which focused on the field trial and field trial revision stages. The reason for focusing on those two stages was that we wanted to know how effective the evaluation tool was in getting the dominant aspects determining the effectiveness of e-learning. The research location was at several health colleges in Bali. Field trials data collection was using a measuring instrument in the form of a questionnaire. The respondents who were involved in conducting field trials were 54 people. Data analysis on the results of field trials was comparing the results of field trials with the standard effectiveness of five’s scale. The results of this study show that the appearance of the digital evaluation tool and the percentage of its effectiveness through field trials was 81.73%, so the tool was categorized as good. The impact of this research on informatics observers/informatics experts is that they will know an innovative evaluation tool used to determine the dominant aspect determining the effectiveness of e-learning based on decision support system methods and Balinese local wisdom.